Design Of Knowledge Management System Of Website Based Cultural - Zuriati Zuriati (Politeknik Negeri Lampung, 2013)
Preservation of national culture should be kept all the time. No maximum knowledge transfer process resulted in the lack of knowledge of the sources of public knowledge about culture. If this happens for a long time, the preservation of culture will be threatened, and extinct. Therefore required a knowledge sharing media as a source of knowledge between communities and indigenous cultures. Knowledge management system (KMS) can be used as a knowledge sharing media among the entire community and traditional leaders as well as experts in the field of culture and other related people. KMS developed web-based, andÂ knowledge sharing process can be optimized, so that people can access knowledge without depending time and place. Traditional leaders are involved in the system so that the quality of existing knowledge on the website is getting better and optimal knowledge sharing process.Â Keywords:Â Culture, knowledge management system, knowledge sharing.